Handling livestock performance data - Metz, T. (Institute of Agricultural Research, 1993)
The major steps of handling data in a research project are listed and the procedures, methods and tools in handling livestock performance data are discussed. Selected problems including lack of focus and purpose, computerization, recording and managing with many small flocks are discussed and livestock information management system (L1MS) - a microcomputer - based animal performance recording package is described.